Predictors of Methamphetamine Use Among Adolescents: Findings From a Midwestern Sample. (April 2015) - Radatz, Dana L.; Vandenberg, Abby L.; Sample, Lisa L.
This study has two primary goals. First, we seek to identify common demographic characteristics and risk factors among adolescent methamphetamine (MA) users, and second, to determine factors that predict MA use among adolescents. A binary logistic regression analysis was performed on data gathered from a 2010 Midwestern state survey administered to 33, 364 middle and high school students. Results indicate that typical adolescent MA users are male, identify racially as "Other, " and are high school upperclassmen. Individual and community risk factors were found to be statistically significant in predicting MA use among adolescents. Specifically, high individual risk level increased the odds of MA use by roughly 9%, and higher community risk-level scores increased the odds by about 3%. Findings suggest that drug prevention efforts should focus attention on adolescent attitudes regarding health consequences and social acceptability of drug use as well as provide afterschool programs/clubs to adolescents.